2009
DOI: 10.1002/jcu.20574
|View full text |Cite
|
Sign up to set email alerts
|

Biliary dilatation secondary to lithiasis in a child affected by Langerhans' cell histiocytosis

Abstract: Langerhans' cell histiocytosis (LCH) is a disease of unknown pathogenesis, caused by clonal proliferation of Langerhans' cells. Liver involvement results in a cholangiopathy, which has the radiologic appearance of sclerosing cholangitis. Only 1 case of obstructive jaundice due to common bile duct stone in a patient with LCH has been described. We present a case of a 31-month-old child with LCH and liver involvement on the waiting list for liver transplantation. During the follow-up, there was a rapid onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Authors of previous studies have reported jaundice in case of LCH in association with hydrops fetalis [11] in a congenital systemic Langerhan cell histiocytosis variant causing excessive hemolysis, hyperbilirubinemia, hypoalbuminemia and failure to thrive in a neonate; as reported by Boccon-Gibod et al, [12]. LCH may also be associated with liver dysfunction with a radiologic appearance of sclerosing cholangitis due to cholangiopathy and stone in the common bile duct causing obstructive jaundice [13]. One case study reports the presence of biliary wall calcification in association with periductal fibrosis and periportal fibrous septa with nodules; consistent with biliary cirrhosis causing jaundice [14].…”
Section: Discussionmentioning
confidence: 85%
“…Authors of previous studies have reported jaundice in case of LCH in association with hydrops fetalis [11] in a congenital systemic Langerhan cell histiocytosis variant causing excessive hemolysis, hyperbilirubinemia, hypoalbuminemia and failure to thrive in a neonate; as reported by Boccon-Gibod et al, [12]. LCH may also be associated with liver dysfunction with a radiologic appearance of sclerosing cholangitis due to cholangiopathy and stone in the common bile duct causing obstructive jaundice [13]. One case study reports the presence of biliary wall calcification in association with periductal fibrosis and periportal fibrous septa with nodules; consistent with biliary cirrhosis causing jaundice [14].…”
Section: Discussionmentioning
confidence: 85%